2002
DOI: 10.1007/s00439-002-0807-2
|View full text |Cite
|
Sign up to set email alerts
|

CTLA-4 gene polymorphisms in systemic lupus erythematosus: a highly significant association with a determinant in the promoter region

Abstract: The cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4; CD 152) is a negative regulator of T-lymphocyte activation. Particular genotypes of the locus encoding the CTLA-4 glycoprotein have been associated with susceptibility to various autoimmune diseases. To determine their role in susceptibility to systemic lupus erythematosus (SLE), we genotyped 130 patients and 200 ethnically matched controls for allelic determinants at four polymorphic sites, viz., three in the promoter region at positions -1722 (T/C), -1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
95
1
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(103 citation statements)
references
References 25 publications
(24 reference statements)
4
95
1
3
Order By: Relevance
“…Importantly elevation in CLTA-4 is not a universal feature of peripheral T cells in patients with autoimmune rheumatic diseases since T cells from RA and PsA showed normal expression levels. Additional support for a role for CTLA-4 in the pathogenesis of lupus comes from genetic studies linking CTLA-4 with SLE [20][21][22][23][24][25][26][27]. One of these polymorphisms impairs the upregulation of CLTA-4 upon T-cell activation [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly elevation in CLTA-4 is not a universal feature of peripheral T cells in patients with autoimmune rheumatic diseases since T cells from RA and PsA showed normal expression levels. Additional support for a role for CTLA-4 in the pathogenesis of lupus comes from genetic studies linking CTLA-4 with SLE [20][21][22][23][24][25][26][27]. One of these polymorphisms impairs the upregulation of CLTA-4 upon T-cell activation [45].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies linking CTLA-4 with SLE provide an additional rationale to investigate the role of CTLA-4 in the pathogenesis of this disease. Indeed, an association between CTLA-4 polymorphisms and lupus has been found in numerous studies around the world [20][21][22][23][24][25][26][27]. In addition, increased CTLA-4 expression has been noted in T cells from patients with SLE [28].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of CTLA-4 on T-cell polarization is further supported by a shifting towards Th2 polarization in germline CTLA-4-deficient mice. 18 Several studies have shown that specific CTLA-4 gene polymorphisms confer susceptibility to several autoimmune diseases, such as Graves' disease, 19 type 1 diabetes, 20 systemic lupus erythematosus 21,22 and SSc. 6,12 In a recent study, we were unable to show any association between CTLA-4 þ 49 polymorphism and SSc in Iranian population.…”
Section: Introductionmentioning
confidence: 99%
“…þ 49 G has been related to multiple diseases, including type 1 diabetes (T1D), 9 rheumatoid arthritis, 10 multiple sclerosis, 11 Graves' disease, 12 asthma, 13 or systemic sclerosis. 14 SNP À1722 has been related to lupus erythematosus in two contradictory studies, 15,16 while the À1661 G variant has been suggested to be associated with T1D. 17 Also, SNPs 6230 G, 10 717 G, 10 242 G and 12 310 T have been related to GD, autoimmune hypothyroidism and T1D.…”
Section: Introductionmentioning
confidence: 99%